Industry 4.0 in process optimization in the industrial sector: Systematic Literature Review - Ore Gavilán, Jheremy Jhonny; Rodríguez Cruces, Laura Paola; Méndez-Gutiérrez, Leidy Lucia; Malpartida Nerio, Antonio (LACCEI, 2025)
This Systematic Literature Review (SLR) addressed the effectiveness of Industry 4.0 methodologies for waste reduction in production processes. However, strengths and weaknesses were identified in the waste elimination process that limit the efficient use of resources. Therefore, the objective was to evaluate the most effective I4.0 technologies and tools to eliminate waste in the production processes of the industrial sector. To achieve this objective, a qualitative, quantitative and mixed research, corresponding to a systematic literature review, was used. Based on the established inclusion and exclusion criteria, 30 open access articles were selected from the Scopus and Scielo databases. The results showed that the most frequent types of waste in production processes are: material defects, waiting times, unnecessary movements and excessive processing. Likewise, it was identified that Artificial Intelligence (AI) was the most implemented technology in the analyzed studies. In conclusion, it was determined that Artificial Intelligence is one of the most efficient tools for process optimization in the industrial sector, reporting substantial improvements of up to 61.00%.